Analysis of the influence of inductance and capacitance on film bulk acoustic wave filter. Issue 5 (January 2021) - Peng, C R; Liu, G; Zhong, H; Shi, Y
Abstract: Film bulk acoustic wave (BAW) filter is a kind of new type filter based on MEMS technology. And it has the advantages of high working frequency, simple manufacturing process, small size, integrating and has become a research hotspot in recent years. Compared with surface acoustic wave filter and ceramic dielectric filter, it has higher operating frequency and Q value. In this paper, the working principle of film bulk acoustic wave filter is briefly analysed, and ADS simulation software is used to further explore the influence of inductance and capacitance on its S parameter.